Comparative evolution of biomass production and lipid accumulation potential of Chlorella species grown in a bubble column photobioreactor. Issue 4 (3rd July 2016) - Sharma, Amit Kumar; Sahoo, Pradeepta Kumar; Singhal, Shailey
ABSTRACT: In the present study, biomass growth and lipid accumulation of five Chlorella species ( Chlorella vulgaris, Chlorella minutissima, Chlorella pyrenoidosa, Chlorella sp.1 and Chlorella sp.2 ) were compared under different nitrogen concentration and sources. In addition, all microalgae species were also grown in a 10 L bubble column photobioreactor under outdoor conditions. The results revealed that Chlorella minutissima have maximum biomass production potential (1.65 g/L) at 35.30 mM nitrogen concentration. Maximum lipid content was recorded for Chlorella vulgaris (21.81%) at 2.21 mM nitrogen concentration. Among different nitrogen sources (NaNo3, KNO3, urea and DAP), urea was observed to be the most economical nitrogen source for large scale biodiesel production feasibility. All species grew well in a 10 L bubble column photo bioreactor under outdoor conditions, but Chlorella vulgaris showed maximum potential for biodiesel production.